Criacionismo e evolucionismo: uma possibilidade de equilíbrio a partir do transformismo de Teilhard de Chardin - Barros, Dirson Maciel de (2008)
This Work aims meanly at demonstrating that there are not so great divergences between biblical Creationism and Evolution Theory, as we look onto the fact on its whole, in view of Fr. Teilhard de Chardin s Transformism, i. e. without disregarding Science, but with a biblical deep knowledge in which it could be possible detecting up scientific truth, revealing itself in a such way that turns possible seeing and feeling deep unity, fusion between matter and spirit. Regarding to biblical Creationism, we have assumed, we have undertaken presenting the two narratives in reference to Creation, described in Genesis and some hermeneutic interpretations about them the two narrations as weel as our adoption, acceptance with regards to second narration in Old and New Testament. As for Evolution Theory, we have been concerned focusing the scientifical viewpoints, with natural divergences among them, in order to make possible a better comprehension, understanding regarding to such a theory content that strives showing up the way human being arose in earth, through a large events, accurences chain, series until Homo Sapiens inexplicable appearance. Since we have delt with we have discussed this equilibrium possibility between these two themes, through Teilhardian transformism, that enables us seeing very clearly that Evolution s missing link is God s Breath that moves on, through complexity consciousness, that leap, jump, inexplicable for Science, moving on the so longed for equilibrium